2022
DOI: 10.3390/molecules27082491
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Synergistic Antitumor Effects Exploited from the Inhibition of Ataxia Telangiectasia and RAD3-Related Protein Kinase (ATR)

Abstract: As one of the key phosphatidylinositol 3-kinase-related kinases (PIKKs) family members, ataxia telangiectasia and RAD3-related protein kinase (ATR) is crucial in maintaining mammalian cell genomic integrity in DNA damage response (DDR) and repair pathways. Dysregulation of ATR has been found across different cancer types. In recent years, the inhibition of ATR has been proven to be effective in cancer therapy in preclinical and clinical studies. Importantly, tumor-specific alterations such as ATM loss and Cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…Although ATR was not quantified in our data, this is supported by previous studies in our group, in which the MM cell line RPMI8226 (classified as "high damage" cells [105]) harboring acquired resistance to melphalan, was exquisitely sensitive to the ATR inhibitor VE-821 [97]. Four ATR inhibitors (berzosertib, ceralasertib, elimusertib and gartisertib) are currently in clinical trials against a variety of solid tumors, but surprisingly few trials encompass hematological malignancies ( [106] and references therein). Noteworthy, however, several of the trials involve co-treatment with PARP1 inhibitors, under the presumption that this would inhibit SSBR and increase replication stress.…”
Section: Dna Repair and Genome Maintenance Proteins Are Upregulated I...supporting
confidence: 82%
“…Although ATR was not quantified in our data, this is supported by previous studies in our group, in which the MM cell line RPMI8226 (classified as "high damage" cells [105]) harboring acquired resistance to melphalan, was exquisitely sensitive to the ATR inhibitor VE-821 [97]. Four ATR inhibitors (berzosertib, ceralasertib, elimusertib and gartisertib) are currently in clinical trials against a variety of solid tumors, but surprisingly few trials encompass hematological malignancies ( [106] and references therein). Noteworthy, however, several of the trials involve co-treatment with PARP1 inhibitors, under the presumption that this would inhibit SSBR and increase replication stress.…”
Section: Dna Repair and Genome Maintenance Proteins Are Upregulated I...supporting
confidence: 82%
“…An extensive description of ATRi development and their clinical trials has been thoroughly reported in recent reviews. 37,81,121,130 Herein, we narrow the description to a selection of medicinal chemistry strategies that led some ATRi entering clinical trials. The structures of ATRi fall into two classes.…”
Section: Usp1mentioning
confidence: 99%
“…ATM, ATR, and DNA-PK are three closely related kinases of the phosphoinositide 3-kinase-related kinase (PIKK) family. ,, These kinases orchestrate DDR at the very early stages, acting as sensors that recognize DSBs and activate the signaling cascade by interacting with many different downstream players (Figure ). , These kinases have been covered extensively by the literature in various reviews. , This work aims to give a brief overview of their function to support the discussion about medicinal chemistry strategies, which has led to recent clinical progress. With regard to detailed clinical trial data, we refer readers to the excellent recent publication by Groelly et al…”
Section: Targeting Sl In the Dna Damage Response (Ddr)mentioning
confidence: 99%
“…Other key members of this family include ataxia telangiectasia mutated (ATM), the mammalian target of rapamycin (mTOR), and the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs), all of which share a high degree of homology in the kinase domain. A number of ATR inhibitors (ATRis) have been identified and several are currently undergoing clinical evaluation in a variety of settings . Common adverse events with ATRi monotherapy include anemia, thrombocytopenia, and neutropenia, the most frequent of which is anemia. , Identifying a highly selective ATRi with a suitable ADME profile as well as selecting the appropriate clinical administration schedule remains an area of active research with the goal of maximizing tolerability and efficacy for patients with genetically selected cancers.…”
Section: Introductionmentioning
confidence: 99%